Transparency-by-design as a foundation for open government. Issue 1 (20th March 2017) - Janssen, Marijn; Matheus, Ricardo; Longo, Justin; Weerakkody, Vishanth
Abstract : Purpose: Many governments are working toward a vision of government-wide transformation that strives to achieve an open, transparent and accountable government while providing responsive services. The purpose of this paper is to clarify the concept of transparency-by-design to advance open government. Design/methodology/approach: The opening of data, the deployment of tools and instruments to engage the public, collaboration among public organizations and between governments and the public are important drivers for open government. The authors review transparency-by-design concepts. Findings: To successfully achieve open government, fundamental changes in practice and new research on governments as open systems are needed. In particular, the creation of "transparency-by-design" is a key aspect in which transparency is a key system development requirement, and the systems ensure that data are disclosed to the public for creating transparency. Research limitations/implications: Although transparency-by-design is an intuitive concept, more research is needed in what constitutes information and communication technology-mediated transparency and how it can be realized. Practical implications: Governments should embrace transparency-by-design to open more data sets and come closer to achieving open government. Originality/value: Transparency-by-design is a new concept that has not given any attention yet in the literature.